Taenia saginata: Production and characterization of monoclonal antibodies against Taenia saginata metacestode antigens - Vicentini-Oliveira, Josy Campanha [UNESP]; Golim, Márjorie de Assis [UNESP]; Paulan, Silvana de Cassia [UNESP]; Biondi, Germano Francisco [UNESP]; Rossi-Ferreira, Rosana [UNESP]; Deffune, Elenice [UNESP]; Nunes, Caris Maroni [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
Cysticercosis is a major cause of economic loss in bovine production due to meat condemnation. Chemotherapy is being used in Brazilian cattle and a diagnostic test to improve the treatment program is desired. We produced monoclonal antibodies against crude (TAEB) and cyst fluid (TAEF) Taenia saginata metacestode antigens using immunized BALB/c mice. After cell fusion, 10 TAEB and nine TAEF hybrids were selected and cloned resulting in 18 IgG(1), and 32 IgM TAEB clones, and 9 IgG(1), and 9 IgM TAEF clones. Ascites was produced and Western blot testing was performed resulting in reactivity to protein fractions of low molecular weight (<18 kDa), 43, 55, 66 and 100 kDa. The indirect immunofluorescence test, with one monoclonal antibody against crude and one against cyst fluid antigens, recognized antigenic fractions of both the scolex and the bladder wall of metacestodes from naturally infected bovine. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Monoclonal antibody (MAb); Taenia saginata; Bovine cysticercosis; Crude antigen; Cyst fluid